1997
DOI: 10.1590/s0074-02761997000200014
|View full text |Cite
|
Sign up to set email alerts
|

Culex gnomatos a New Species of the Spissipes Section of Culex (Melanoconion) (Diptera: Culicidae) from the Amazon Region

Abstract: The adult male and female of Culex (Melanoconion) gnomatos n. sp. are described and compared with Cx. vomerifer Komp, Cx. portesi Senevet & Abonnenc and Cx. sacchettae Sirivanakarn & Jakob. Available data about distribution and bionomics are presente

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 1 publication
4
53
0
4
Order By: Relevance
“…Specimens collected were frozen in liquid nitrogen for virus isolation. IdentiÞcation of mosquitoes followed Lane (1953), Bram (1967), Reinert (1975), Berlin and Belkin (1980), Sirivanakarn (1983), Pecor et al (1992), Judd (1996), Sallum and Forattini (1996), Harbach and Kitching (1998), and our own collections in the Laboratorio de Biologṍa de Vectores (LBV in Guimarães 1997). Results were presented as means and standard errors.…”
Section: Methodsmentioning
confidence: 69%
“…Specimens collected were frozen in liquid nitrogen for virus isolation. IdentiÞcation of mosquitoes followed Lane (1953), Bram (1967), Reinert (1975), Berlin and Belkin (1980), Sirivanakarn (1983), Pecor et al (1992), Judd (1996), Sallum and Forattini (1996), Harbach and Kitching (1998), and our own collections in the Laboratorio de Biologṍa de Vectores (LBV in Guimarães 1997). Results were presented as means and standard errors.…”
Section: Methodsmentioning
confidence: 69%
“…Pecor et al (1992) suggested that the Ocellatus Section (previously considered within the subgenus Microculex) did not belong to Melanoconion, and it remains without subgeneric assignment. Later, Sallum and Forattini (1996) made the Þrst revision for the Spissipes Section based on morphological characters of the adults male and female (including species identiÞcation keys). Most of these taxonomic studies have emphasized the importance of morphological characters in a traditional, noncladistic, or nonphylogenetic treatment.…”
mentioning
confidence: 99%
“…12 In each village, 10 households were also selected, where 10 Centers for Disease Control and Prevention light traps baited with octanol as an attractant and four encephalitis vector survey (CO 2 ) mosquito traps (BioQuip Products, Rancho Dominguez, CA) were placed. The following day, mosquitoes were collected in the field, transported to the base camp where they were anesthetized, identified to the genus level using taxonomic keys 13 and then were placed in cryovials for storage in liquid nitrogen. Virus isolation.…”
mentioning
confidence: 99%